2014
DOI: 10.1530/rep-13-0552
|View full text |Cite
|
Sign up to set email alerts
|

Role of iron overload-induced macrophage apoptosis in the pathogenesis of peritoneal endometriosis

Abstract: This article presents an overview of the involvement of iron overload-induced nitric oxide (NO) overproduction in apoptosis of peritoneal macrophages of women with endometriosis. We have postulated that the peritoneal iron overload originated from retrograde menstruation or bleeding lesions in the ectopic endometrium, which may contribute to the development of endometriosis by a wide range of mechanisms, including oxidative damage and chronic inflammation. Excessive NO production may also be associated with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 114 publications
(122 reference statements)
1
20
0
1
Order By: Relevance
“…17, 18, 19, 20 The co-culture with ESCs led to a threefold upregulation of IL-27 + monocytes (Figure 3a). In addition, LPS stimulation significantly increased IL-27 levels in monocytes (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…17, 18, 19, 20 The co-culture with ESCs led to a threefold upregulation of IL-27 + monocytes (Figure 3a). In addition, LPS stimulation significantly increased IL-27 levels in monocytes (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies have focused on the importance of immunological imbalances in women with endometriosis. It has been confirmed that, a permissive peritoneal environment may be associated with the initiation and development of endometriosis (1)(2)(3)11). Rather than effectively removing the retrograde endometrial fragments in the pelvic cavity, the tolerant environment facilitates the implantation, neo-angiogenesis and proliferation of ectopic endometrial tissue (15,16).…”
Section: Discussionmentioning
confidence: 95%
“…Inflammation of the surrounding pelvic microenvironment is thought to have an important role in the initiation and progression of endometriosis, in addition to ovarian steroid hormones (1). The ectopic growth of 'lesions', consisting of endometrial cells outside the uterine cavity, stimulate an inflammatory response, which initiates the activation of macrophages and leads to increased concentrations of cytokines and growth factors in the peritoneal fluid (2,3). Indoleamine 2,3-dioxygenase (IDO1) is an intracellular heme enzyme that catalyzes the initial and rate-limiting step in the metabolism of the essential amino acid tryptophan in the kynurenine pathway.…”
Section: Introductionmentioning
confidence: 99%
“…However, these theories remain controversial. 2,3 Endometriosis develops in 5% to 10% of women of reproductive age, 4 and in Cipto Mangunkusumo Hospital (CMH), Jakarta, in 2010, endometriosis accounted for 42.62% of all benign gynecologic abnormalities. 5 The clinical manifestations are varied and range from no symptoms to debilitating pain in about 40% to 60% of patients with endometriosis-associated dysmenorrhea.…”
Section: Introductionmentioning
confidence: 99%